Early results of fluorescence lymphatic mapping for right colon cancer: a case-matched study - Şen, Murat; Yılmazlar, Tuncay; Sığırlı, Deniz; Işık, Özgen (The European Research Journal, 2024)
Objectives: The complete mesocolic excision (CME) technique has been described to improve the surgical outcomes of colon cancer. Collecting more lymph nodes is one of the goals of CME. In our study, indocyanine green (ICG) injection was applied to the anterior and posterior walls at certain levels of the right colon. The aim of this study is to determine the impact of lymphangiography in right colon cancer surgery. Methods: The data of patients were analyzed who underwent colectomy surgery between 1.1.2018-1.1.2022 and using our mapping technique. A case-match study was performed at a ratio of 1:2 (Study group [group S; n =10], Control group [group C; n = 20]). Case-matched criteria were age +/-10, T stage +/-1, and tumor location. Results: There were no differences in terms of age, the American Society of Anesthesiologists score, tumor location, tumor T and N stages, and pathological markers affecting prognosis between the groups. Although 10% of intraoperative complications were seen in group C, it was not statistically significant (p = 0.540). After lymphangiography, lymph nodes containing ICG were detected in the resection site and these lymph nodes were sent to pathology in separate containers. Considering the number of lymph nodes sent separately, it was determined that significantly more lymph nodes were sent in the group S (p = 0.001). Conclusions: We have shown that the ICG mapping can be applied safely in the surgical treatment of right colon cancer.